Lymph node ratio as a prognostic factor in elderly patients with pathological N1 non-small cell lung cancer. Issue 4 (2nd December 2010) - Wisnivesky, Juan P; Arciniega, Jacqueline; Mhango, Grace; Mandeli, John; Halm, Ethan A
Abstract : Background: Lymph node (LN) metastasis is an important predictor of survival for patients with non-small cell lung cancer (NSCLC). However, the prognostic significance of the extent of LN involvement among patients with N1 disease remains unknown. A study was undertaken to evaluate whether involvement of a higher number of N1 LNs is associated with worse survival independent of known prognostic factors. Methods: Using the Surveillance, Epidemiology and End Results-Medicare database, 1682 resected patients with N1 NSCLC diagnosed between 1992 and 2005 were identified. As the number of positive LNs is confounded by the total number of LNs sampled, the cases were classified into three groups according to the ratio of positive to total number of LNs removed (LN ratio (LNR)): ≤0.15, 0.16–0.5 and >0.5. Lung cancer-specific and overall survival was compared between these groups using Kaplan–Meier curves. Stratified and Cox regression analyses were used to evaluate the relationship between the LNR and survival after adjusting for potential confounders. Results: Lung cancer-specific and overall survival was lower among patients with a high LNR (p<0.0001 for both comparisons). Median lung cancer-specific survival was 47 months, 37 months and 21 months for patients in the ≤0.15, 0.16–0.5 and >0.5 LNR groups, respectively. In stratified and adjusted analyses, a higher LNR was also associated with worse lung cancer-specific and overall survival. Conclusions: The extent of LN involvement provides independent prognostic information in patients with N1 NSCLC. This information may be used to identify patients at high risk of recurrence who may benefit from aggressive postoperative therapy.